Cigarette smoking and age of menopause - Mahmood Shakir Imarah, Ishraq (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: To identify the effect of cigarette smoking on women's age of menopause. Earlier time at menopause increased women morbidity and mortality rates. Unhealthy lifestyle had a negative impact on women's age at menopause. Methods: Present study was a retrospective cross-sectional study implemented at outpatients' clinics of Maternity Teaching hospital in Erbil city, Kurdistan region-Iraq in period of six months from 1st of January to 30th of June 2024on sample of 280 women experienced menopause. The menopause of studied women was confirmed by absence of menstrual cycle for at least one year with experiencing menopause symptoms. Results: Mean age at menopause was (46.8 years); premature menopause was recorded in 10% of women and early menopause was present in 21.4% of them. A highly significant association was observed between current smoking status of women and earlier menopause (P <0.001). Longer smoking duration of women with positive smoking history was related significantly to earlier menopause (P <0.001).Single marital status and nulliparity may play role in developing early menopausal age. Conclusion: The prevalence of premature menopause in women experienced menopause is high. The smoking and duration of smoking are risk factors for earlier age at menopause.